2017
DOI: 10.1016/j.ophtha.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Temporal Lamina Cribrosa Defects in Myopic Eyes with Glaucoma and Their Association with Visual Field Defects

Abstract: Myopic eyes with OAG exhibited LC defects and large pores at similar locations as those without OAG, but in greater numbers, suggesting that these focal alternations of the LC in myopic eyes may evolve into larger defects when glaucoma develops in the eye. The number of LC defects, which was related to the optic disc tilt angle, was associated significantly with glaucomatous VF defects in both severity and location. This suggests that myopia may influence glaucomatous VF defects through optic disc tilt by way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…It has been reported that small disc size and long AXL might be related to the development of the focal LC defect. 33,34 In this study, the focal γPPA group had a significantly larger width of both the horizontal and vertical optic disc widths and shorter AXL than the conventional γPPA group. Moreover, the values in the focal γPPA group were similar to those in the no γPPA group (Table 2).…”
Section: Discussionmentioning
confidence: 50%
“…It has been reported that small disc size and long AXL might be related to the development of the focal LC defect. 33,34 In this study, the focal γPPA group had a significantly larger width of both the horizontal and vertical optic disc widths and shorter AXL than the conventional γPPA group. Moreover, the values in the focal γPPA group were similar to those in the no γPPA group (Table 2).…”
Section: Discussionmentioning
confidence: 50%
“…A focal LC defect was defined as a loss of high reflectivity from the anterior-to-posterior border of the full-thickness LC on B-scan images. To avoid false-positives, the defects were required to have had a maximal diameter greater than 100 μm and a depth greater than 30 μm, and to have been present in two adjacent B-scans 14,15 . Shadows were differentiated from LC defects on the basis of their characteristic signal void behind the vessels and tissues.…”
Section: Detection Of Lamina Cribrosa Defectmentioning
confidence: 99%
“…Optic disc tilt in highly myopic eyes deform the lamina cribrosa (LC) and may obstruct axoplasmic flow within the optic nerve head, thus promoting glaucomatous optic nerve damage 75. Imaging of the LC integrity in these eyes may yield information on the risk of glaucoma 11.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging of the LC integrity in these eyes may yield information on the risk of glaucoma 11. Sawada et al 75 evaluated LC defects in myopic eyes with and without open-angle glaucoma using enhanced depth OCT and found these defects to be related to the optic disc tilt angle and were associated with glaucomatous visual field defects in both location and severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation